Impacts of HIV-1 Subtype Diversity on Long-Term Clinical Outcomes in Antiretroviral Therapy in Guangxi, China. (15th April 2022) - Jiang, He; Lan, Guanghua; Zhu, Qiuying; Feng, Yi; Liang, Shujia; Li, Jianjun; Zhou, Xinjuan; Lin, Mei; Shao, Yiming
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Comprehensively estimating the impacts of HIV-1 subtype diversity on long-term clinical outcomes during antiretroviral therapy (ART) can help inform program recommendations. Methods: The HIV-1 sequence data and clinical records of 5950 patients from all 14 prefectures in Guangxi, China, during 2008–2020 were included. Evolutional trends of CD4+ T-lymphocyte count and viral load were explored, and the effects of HIV-1 subtypes on clinical outcomes were estimated by the Cox proportional hazards model. The polymorphisms involved in drug resistance mutation were analyzed. Results: Compared with patients with CRF07_BC, patients with CRF01_AE and CRF08_BC showed poor immunologic and virologic responses to antiretroviral therapy. Although the median expected time from ART initiation to virologic suppression for all patients was approximately 12 months, patients with CRF01_AE and CRF08_BC had a long time to achieve immune recovery and a short time to occur immunologic failure, compared with patients with CRF07_BC. Adjusted analysis showed that both CRF01_AE and CRF08_BC were the negative factors in immune recovery and long-term mortality. In addition, CRF08_BC was a negative factor in virologic suppression and a risk factor of virologic failure. This poor virologic response might result from the high prevalence of drug resistance mutation in CRF08_BC. Conclusions: Compared with patients with CRF07_BC, patients with CRF01_AE could benefit more from immediate ART, and patients with CRF08_BC are more suitable for PI-based regimens. These data emphasize the importance of routine HIV-1 genotyping before ART, immediate ART, and personalized ART regimens to improve the prognosis for patients undergoing ART.